A fundamental evaluation of the atmospheric pre-leaching section of the nickel-copper matte treatment process - Lamya, Rodrick Mulenga (Stellenbosch : University of Stellenbosch, 2008)
Thesis (PhD (Process Engineering))--University of Stellenbosch, 2007.